PEMANFAATAN LIMBAH ORGANIK (ECOENZIM) SEBAGAI IMPLEMENTASI GREEN TOURISM DESTINASI WISATA NGURBLOAT - Pradina Sukirno; Melissa Justin Renjaan; Yanto Anwar; Kusmawati Bugis; Simson Metungun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2026)
The community service activity entitled Utilization of Organic Waste (Ecoenzyme) as an Implementation of Green Tourism at the Ngurbloat Tourist Destination was carried out with the aim of training the skills of business actors in the Ngurbloat destination in managing organic waste as well as for environmental awareness as the image of ngurbloat as a clean and sustainable environmental tourism. The method used was socialization and training involving 20 culinary business actors at Ngurbloat Beach. This activity also involved the village government and BUMO as the manager of the tourist location and the BUMN House for coaching business actors. The final result of this activity was the harvest of ecoenzyme and the manufacture of natural cleaners as well as the publication of a community service journal. This activity is expected to be able to empower business actors in Ngurbloat and make them agents of change in the problem of organic waste.